pengaruh inovasi produk dan kepuasan konsumen terhadap keputusan pembelian pada banana pop kota bima - Silvaazmiatun Asmi; intisari haryanti (Universitas Sarjanawiyata Tamansiswa, 2022)
This study aims to examine and determine the effect of product inovation on product purchasing decisions at Banana Pop Bima City, and examine the effect of consumer satisfaction on purchasing decisions. Population is not known sure, therefore the sampling technique is done by purpusive sampling in determining the sample. The questionnaires that were successfully collected were 100 questionnaires. The results showed that there was a significant effect of product innovation on purchasing decisions. The variable of consumer satisfaction with purchasing decisions has no significant effect. Innovation must continue to be done to maintain product purchase decisions at Banana Pop Bima City.